2005
DOI: 10.1007/s00020-005-1386-0
|View full text |Cite
|
Sign up to set email alerts
|

On the Isolated Points of the Spectrum of Paranormal Operators

Abstract: For paranormal operator T on a separable complex Hilbert space H, we show that (1) Weyl's theorem holds for T , i.e., σ(T ) \ w(T ) = π00(T ) and (2) every Riesz idempotent E with respect to a non-zero isolated point λ of σ(T ) is self-adjoint(i.e., it is an orthogonal projection) and satisfies that ranE = ker(T − λ) = ker(T − λ) * .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…This result has since been generalized by many mathematicians ( [1], [6], [4], [13]). In particular we should recall Duggal's result ( [2]; [3]) for an extended class of non-hyponormal operators.…”
Section: Introductionmentioning
confidence: 86%
“…This result has since been generalized by many mathematicians ( [1], [6], [4], [13]). In particular we should recall Duggal's result ( [2]; [3]) for an extended class of non-hyponormal operators.…”
Section: Introductionmentioning
confidence: 86%
“…In [9], Uchiyama showed that if T is paranormal, i.e., T ∈ P(2), then Weyl's theorem holds for T , and if λ is a non-zero isolated point of σ(T ), then the Riesz idempotent E λ of T with respect to λ is self-adjoint and…”
Section: The Class P(n)mentioning
confidence: 99%
“…In [9], Uchiyama proved that for every paranormal operator T and each isolated point λ of σ(T ) the Riesz idempotent E λ satisfies that…”
Section: Introduction Let B(h) Be the Set Of All Bounded Linear Operamentioning
confidence: 99%
See 1 more Smart Citation
“…We cite [8,[14][15][16][17][18][19][20][21][22]. In this paper, we will discuss several spectral properties of class wF(p,r, q) for p > 0, r > 0, p + r ≤ 1, and q ≥ 1.…”
Section: Introduced W-hyponormal Operators Defined By | T| ≥ |T| ≥ |( T)mentioning
confidence: 99%